The Impact of Community-Based Health Insurance on Household's Welfare in Chilga District, Amhara Regional State, Ethiopia - Asfaw, Dagmawe Menelek; Shifaw, Sirage Mohammed; Belete, Atinkugn Assefa; Aychiluhm, Setognal Birara (Frontiers in Public Health, 2022)
Household welfare is depleted by catastrophic health expenditure through forcing families to reduce the consumption of necessity goods and services, underutilization health services, and of finally fall into the poverty trap. To mitigate such a problem the Government of Ethiopia launched CBHI schemes. Therefore, this study investigates the household welfare impact of CBHI in Chilga district. A multi-stage sampling technique was used to select 531 households (of which 356 treated and 175 control groups). Probit, and propensity score matching (PSM) were used to analyze the data. Probit model revealed: level of education, access to credit, chronic disease, insurance premium, awareness, distance to health service, and health service waiting time are significant determinates for to be insured in CBHI. The PSM method revealed that the insured households associated with visits increased by 2.6 times, reduced per capita health expenditure by 17-14 percentage points, increased the per capita consumption of non-food items by 12-14 percentage points, increased the per capita consumption of food items 12-13 percentage points in a given matching algorithm compared to the counterparts. Therefore, CBHI has enhanced service utilization, reducing per capita health expenditure and increasing consumption per capita, in the general, it improved household welfare. To this end, the results of this study suggested that the government (ministry of health) and concerned bodies (like NGOs) should: extend the coverage and accessibility of CBHI schemes, create aware to the society about CBHI, and subsidize premium costs of the poor.